2016
DOI: 10.5897/ajmr2015.7802
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem resistance mechanisms among blood isolates of Klebsiella pneumoniae and Escherichia coli

Abstract: The purpose of this study was to characterize the different mechanisms of carbapenem resistance among blood isolates of Klebsiella pneumoniae and Escherichia coli. Meropenem resistant isolates were included. Antimicrobial susceptibility testing, phenotypic and genotypic detection of carbapenemase production were performed. Genetic relatedness of bla NDM-1 producers was determined by pulsed-filed gel electrophoresis (PFGE) typing. The relatedness of bla NDM-1 carrying plasmids was studied by plasmid restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…15 In another study Mohamudha RP et al, also found that the distributions of the sources of the isolates were: urine 37% (n=39), blood 22.3% (n=23), wound discharge 11.7% (n=12), peritoneal fluid 5.8% (n=6), ascitic fluid 10.7% (n=11), tracheal aspirate 6.8% (n=7), and sputum 4.9% (n=5). 16 Nagaraj S et al, had comparable findings where they observed that the carbapenem-resistant organisms were isolated mainly from urine samples up to 42% (n = 21), followed by wound discharge 18% and respiratory secretions 16%. 17 The MHT screening test for carbapenems is currently proposed by the clinical and laboratory standards institute (CLSI) for phenotypic screening of carbapenemases producers.…”
Section: Discussionmentioning
confidence: 77%
“…15 In another study Mohamudha RP et al, also found that the distributions of the sources of the isolates were: urine 37% (n=39), blood 22.3% (n=23), wound discharge 11.7% (n=12), peritoneal fluid 5.8% (n=6), ascitic fluid 10.7% (n=11), tracheal aspirate 6.8% (n=7), and sputum 4.9% (n=5). 16 Nagaraj S et al, had comparable findings where they observed that the carbapenem-resistant organisms were isolated mainly from urine samples up to 42% (n = 21), followed by wound discharge 18% and respiratory secretions 16%. 17 The MHT screening test for carbapenems is currently proposed by the clinical and laboratory standards institute (CLSI) for phenotypic screening of carbapenemases producers.…”
Section: Discussionmentioning
confidence: 77%
“…In a study by Amjad A et al 24 out of 100 isolates which were carbapenem intermediate or sensitive, 69% showed the presence of carbapenemase by MHT which is similar with this study. In the study by Mahajan G et al 16 47.6% of the isolates were found to produce carbapenemase enzyme by MHT and the remaining 22 strains were found to be carbapenemase negative. In a study by Rajkumar MS et al 25 among the thirty seven meropenem resistant isolates, MHT was positive for 91.89% of the isolates.…”
Section: Discussionmentioning
confidence: 95%
“…Resistance to carbapenem in this study is low compared to studies by various authors from India. In a study by Bijayini Behera et al 16 at the All India Institute of Medical Sciences, New Delhi, carbapenem resistance was found to be 69%, which much on the higher side.…”
Section: Discussionmentioning
confidence: 98%
“…Studies performed by Rahamathulla et al (2016) showed that resistance to meropenem is an increasing public health problem because this antibiotic is one of the last resources for the treatment of infections in hospitals. Rasmussen et al (1996) reported that this serious problem is associated with genes encoding carbapenemases on plasmids or transposons in carbapenem-resistant bacteria.…”
Section: Discussionmentioning
confidence: 99%